'Aamchi Mumbai' in Rohinton Mistry's fiction: urban ecology, filth and foliage. Issue 2 (2nd April 2020) - Daithota Bhat, Shilpa
ABSTRACT: This article is an examination of the representations of filth and foliage, dirtscapes and the urbanisation process in Rohinton Mistry's Such a Long Journey and A Fine Balance fictional works that portray, via spatial and temporal structuration, the devastation of nature and rapid industrialisation in Mumbai. Through Sullivan's 'dirt theory', I explore how Mistry gestures at the epistemological paradigms, intricate relationships and overlapping spheres of technological development and nature. The idea of the colonial, community and personal pieties in the Indian subcontinent post-independence, forge trajectories of urban migration for education and job purposes, articulating agency and power relations. The social and religious orientations will be analysed in the theoretical and conceptual frameworks of ecology, religious perceptions and urbanisation offering the space for critically appraising the subject of ecofiction in ' Aamchi Mumbai ' – a phrase that gestures at both place-making and individual existence.